2005
DOI: 10.1097/01.wnp.0000150880.19561.6f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Interictal Spikes and Artifactual Data Through Orthogonal Transformations

Abstract: This study introduces an integrated algorithm based on the Walsh transform to detect interictal spikes and artifactual data in epileptic patients using recorded EEG data. The algorithm proposes a unique mathematical use of Walsh-transformed EEG signals to identify those criteria that best define the morphologic characteristics of interictal spikes. EEG recordings were accomplished using the 10-20 system interfaced with the Electrical Source Imaging System with 256 channels (ESI-256) for enhanced preprocessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 23 publications
2
23
0
1
Order By: Relevance
“…14,18,24,26,30 Researchers have thus considered different approaches using a diversity of linear and nonlinear parameters in order to automate processes of seizure detection, eliciting a better understanding of the chaotic dynamics in biological systems, 6,15,21,23 and where promising results have been substantiated. 1,2,16,29,31 In using subdural EEG data in this study, we have taken into consideration the fact that there is a considerable attenuation effect of the skull on the scalp EEG. This data generally reveal very little fast activity exceeding the beta range [>30 Hz], limiting as a result the application scope of seizure detection algorithms that rely on scalp EEG recordings since there is a limitation in the use of higher frequency components.…”
Section: Introductionmentioning
confidence: 99%
“…14,18,24,26,30 Researchers have thus considered different approaches using a diversity of linear and nonlinear parameters in order to automate processes of seizure detection, eliciting a better understanding of the chaotic dynamics in biological systems, 6,15,21,23 and where promising results have been substantiated. 1,2,16,29,31 In using subdural EEG data in this study, we have taken into consideration the fact that there is a considerable attenuation effect of the skull on the scalp EEG. This data generally reveal very little fast activity exceeding the beta range [>30 Hz], limiting as a result the application scope of seizure detection algorithms that rely on scalp EEG recordings since there is a limitation in the use of higher frequency components.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the most discriminative features for neonatal seizure detection 1 are morphological based features, such as amplitude, shape and duration of waveforms. In addition, time domain features such as statistical features (Adjouadi et al, 2005), Hjorth's descriptors (Hjorth, 1970), nonlinear features (Kannathal, Acharya, Lim, & Sadasivan, 2005;McSharry, et al, 2002)-correlation dimension (Elger & Lehnertz, 1998), Lyapunov exponent Ubeyli, 2006;Ubeyli, 2010b) and other features obtained from convolution kernels (Adjouadi et al, 2004), eigenvector methods (Naghsh-Nilchi & Aghashahi, 2010 ; Ubeyli, 2008aUbeyli, , 2008bUbeyli, , 2009a, principal component analysis (PCA) (Ghosh-Dastidar, Adeli, & Dadmehr, 2008;Hesse & James, 2007;James & Hesse, 2005;Polat & Gunes, 2008a;Subasi & Gursoy, 2010), ICA (Hesse & James, 2007;James & Hesse, 2005;Subasi & Gursoy, 2010), crosscorrelation function (Chandaka, Chatterjee, & Munshi, 2009;Iscan, et al, 2011), and entropy (Guo, Rivero, Dorado, et al, 2010;Kannathal, Choo, Acharya, & Sadasivan, 2005;Liang, Wang, & Chang, 2010;Naghsh-Nilchi & Aghashahi, 2010 ;H. Ocak, 2009;Srinivasan, Eswaran, & Sriraam, 2007;Wang, et al, 2011) have been proposed to characterize the EEG signal.…”
Section: Automated Epileptic Seizure Analysismentioning
confidence: 99%
“…A difference operator can be used but they have a serious drawback of being highly susceptible to noise, and thus a smoothing operator need to be included to improve the differentiator's signal to noise ratio (SNR). The Walsh differentiation method (Adjouadi et al, 2004(Adjouadi et al, , 2005Weide et al, 1978) was utilized to overcome the problem, as described in the following section.…”
Section: Amuse Algorithm -Noise Components Filteringmentioning
confidence: 99%
“…Detection of the peak that coincides with the occurrence of the SSEP was automated using the Walsh transformation method (Weide et al, 1978;Smith, 1981;Adjouadi et al, 2004Adjouadi et al, , 2005 to indicate the evoked potential response.…”
Section: Amuse Algorithmmentioning
confidence: 99%
See 1 more Smart Citation